2023
DOI: 10.5194/nhess-23-525-2023
|View full text |Cite
|
Sign up to set email alerts
|

A multi-disciplinary analysis of the exceptional flood event of July 2021 in central Europe – Part 1: Event description and analysis

Abstract: Abstract. The July 2021 flood in central Europe was one of the five costliest disasters in Europe in the last half century, with an estimated total damage of EUR 32 billion. The aim of this study is to analyze and assess the flood within an interdisciplinary approach along its entire process chain: the synoptic setting of the atmospheric pressure fields, the processes causing the high rainfall totals, the extraordinary streamflows and water levels in the affected catchments, the hydro-morphological effects, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 59 publications
4
40
0
Order By: Relevance
“…Similar observations were made for the July 2021 event (e.g. Mohr et al, 2023). Given the exceptional xWEI values of both the August 2002 and the July 2021 events, it might be worthy to discuss, in the future, whether heavy precipitation events that are extreme across scales could be framed as hydrometeorological compound events.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Similar observations were made for the July 2021 event (e.g. Mohr et al, 2023). Given the exceptional xWEI values of both the August 2002 and the July 2021 events, it might be worthy to discuss, in the future, whether heavy precipitation events that are extreme across scales could be framed as hydrometeorological compound events.…”
Section: Discussionsupporting
confidence: 55%
“…Numerous studies have been published since the event, e.g. related to meteorological, hydrological and impact-related aspects (Mohr et al, 2023); hydro-geomorphological processes (Dietze et al, 2022); or early warning (Fekete and Sandholz, 2021;Thieken et al, 2022a). The temporal development of the event (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While research [88, [94][95][96] and reports [97] focus on the shocking amounts of debris transported by the rivers, ultimately exacerbating the event by clogging bridges that failed later on, little attention has been paid to the ne fraction of the ood sediments. However, as the transport capacity for ne materials is particularly high, they are spread over larger areas.…”
Section: Methodsmentioning
confidence: 99%
“…Taszarek et al (2019) showed based on European Severe Weather Database reports (ESWD; Dotzek et al, 2009) that much of Germany reports 8 or more days per year with heavy convective precipitation (their Figure 7). Recent events such as the exceptional floods of Central Europe in July 2021 (Mohr et al, 2023), which was exacerbated by embedded convection, highlight the need for further information on the underlying processes that lead to heavy convective precipitation.…”
Section: Introductionmentioning
confidence: 99%